Characterization of Zeolitic Mineral for Developing Nanostructured Materials - Rodríguez-Fuentes, G.; Rodríguez-Iznaga, I. (Revista Cubana de Física; Vol 26 No 1 (2009): Cuban Nanotechnology 2009, 2009)
The study of representative samples from two natural clinoptilolite deposits has shown that the morphology of the crystal, produces a significant influence on the ion exchange process of the zeolite. The determined kinetic parameters of the ammonium exchange at room temperature and 100º C are different. The activation energy of the exchange process is 14.1 KJ mol -1 when the ammonium was exchanged in the sample representative of the mineral from a drill hole (0 - 30 meters), while the energy of the same process is about 3 KJ.mol-1 for a sample representative of the weathered horizon (0 - 7 meters). The kinetic parameters of the exchange of Ni 2+ and Co 2+ are different for the samples from both deposits even when the samples were extracted from similar section, as a consequence of the crystal morphology.